Kwentong Pambata: Interactive Storybook for Filipino Fables, Legends, Parables and Short Stories - Marivic Reyes Mitschek; Maureen Joy M. Nolasco; Maria Cristina DC Pindot; Romina J. Sy (Celt: A Journal of Culture, English Language Teaching & Literature, 2017)
This paper focused on the development and evaluation of a mobile application in which children could interact, be entertained, and especially be educated at the same time. It was mainly designed for children, parents/guardians, and teachers as well. The interactive storybook which was created was different from those available in the market.  Kwentong Pambata is a children’s storybook application designed for Android devices that features Filipino legends, fables, parables and short stories designed for Filipino children and children all over the world. It portrays Filipino values, traditions and character which contains moral lesson at the end of each story that would educate children’s view in life, their characters, moral uprightness, and values. It is a storybook which contains fun pictures, texts, and sounds that kids will truly enjoy. The goal of the study is to develop an Android application that children could interact, learn, read, be entertained, improve and develop children’s imagination and comprehension skills at an early age, and to promote Filipino stories and moral values. Kwentong Pambata application was developed using ActionScript 3.0. and Adobe Flash CS5.5. The application has 3 different language translations such as Filipino, English, and Mandarin. The proponents used ADDIE model for the development of the application. After the development, the application was evaluated. The total number of 40 respondents which were selected through probability sampling is used for the evaluation process. The application was evaluated according to its Usability, Reliability, Efficiency and Graphical User Interface (GUI).  The evaluation questionnaire showed that the application was rated as very satisfactory with the help of the respondents and was improved throughout its revisions.